2004
DOI: 10.1128/mcb.24.11.5069-5079.2004
|View full text |Cite
|
Sign up to set email alerts
|

NHERF2 Specifically Interacts with LPA2 Receptor and Defines the Specificity and Efficiency of Receptor-Mediated Phospholipase C-β3 Activation

Abstract: Lysophosphatidic acid (LPA) activates a family of cognate G protein-coupled receptors and is involved in various pathophysiological processes. However, it is not clearly understood how these LPA receptors are specifically coupled to their downstream signaling molecules. This study found that LPA 2 , but not the other LPA receptor isoforms, specifically interacts with Na ؉ /H ؉ exchanger regulatory factor2 (NHERF2). In addition, the interaction between them requires the C-terminal PDZ domain-binding motif of LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 45 publications
4
88
2
Order By: Relevance
“…We have previously shown that knockdown of NHERF2 expression in Caco-2 cells by RNA interference drastically down-regulates the LPA 2 -Gα i -Akt pathway and induction of IL-8 [21]. Moreover, over-expression of NHERF2 reconstitutes the signaling mediated by LPA 2 [23]. Collectively these data demonstrate that displacement of the LPA 2 -NHERF2 interaction severely perturbs the cellular signaling mediated by LPA 2 .…”
Section: Protection Of Caco-2 From Etoposide-induced Apoptosis Is Depmentioning
confidence: 53%
See 3 more Smart Citations
“…We have previously shown that knockdown of NHERF2 expression in Caco-2 cells by RNA interference drastically down-regulates the LPA 2 -Gα i -Akt pathway and induction of IL-8 [21]. Moreover, over-expression of NHERF2 reconstitutes the signaling mediated by LPA 2 [23]. Collectively these data demonstrate that displacement of the LPA 2 -NHERF2 interaction severely perturbs the cellular signaling mediated by LPA 2 .…”
Section: Protection Of Caco-2 From Etoposide-induced Apoptosis Is Depmentioning
confidence: 53%
“…Herein, we show that LPA provides survival signals to Caco-2 cells, protecting cells from etoposide-induced apoptosis via a NHERF2-dependent mechanism. It has previously been shown that NHERF2 interacts with LPA 2 , but not other LPA receptors, and plays a pivotal role in regulation of cellular signaling elicited by LPA 2 [21,23]. Knockdown of NHERF2 in Caco-2 and HeLa cells drastically compromised LPA 2 -mediated signaling, such as activation of Akt, Erk, and PLCβ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All three EDG-family LPA GPCRs activate MAPK [47][48][49][50]. The transient MAPK activation observed in RH7777 cells and DKO cells in response to LPA temporally and pharmacologically resembles the cellular blebbing response; it seems likely these two processes are coupled, although the exact relationship requires further clarification.…”
Section: Discussionmentioning
confidence: 99%